2023
DOI: 10.3847/1538-4357/acdc17
|View full text |Cite
|
Sign up to set email alerts
|

Non-field-aligned Proton Beams and Their Roles in the Growth of Fast Magnetosonic/Whistler Waves: Solar Orbiter Observations

Abstract: The proton beam is an important population of the non-Maxwellian proton velocity distribution in the solar wind, but its role in wave activity remains unclear. In particular, the velocity vector of the proton beam and its influence on wave growth/damping have not been addressed before. Here we explore the origin and the associated particle dynamics of a kinetic wave event in the solar wind by analyzing measurements from Solar Orbiter and comparing them with theoretical predictions from linear Vlasov theory. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The meticulous analysis performed by these authors revealed that the peak of the probability density function of the angle between the proton beam drift velocity and the local field was a few degrees, remarkably in agreement with our findings. This observation is interesting because, despite the 5°angular resolution of PAS, we can discern plasma parameters with an uncertainty of under 5°, as remarked by Zhu et al (2023). It would be intriguing to explore whether these fluctuations have a comparable impact on the misalignment between the alpha core and alpha beam velocity drifts.…”
Section: Velocity Driftmentioning
confidence: 64%
See 1 more Smart Citation
“…The meticulous analysis performed by these authors revealed that the peak of the probability density function of the angle between the proton beam drift velocity and the local field was a few degrees, remarkably in agreement with our findings. This observation is interesting because, despite the 5°angular resolution of PAS, we can discern plasma parameters with an uncertainty of under 5°, as remarked by Zhu et al (2023). It would be intriguing to explore whether these fluctuations have a comparable impact on the misalignment between the alpha core and alpha beam velocity drifts.…”
Section: Velocity Driftmentioning
confidence: 64%
“…According to Zhu et al (2023), linear Vlasov theory posits that the presence of fast magnetosonic and/or whistler waves induces fluctuations in the velocities of both the proton core and beam, consequently disrupting the alignment of their velocity drift with the magnetic field. Subsequent analysis by the same authors, leveraging Solar Orbiter observations, revealed distinct time intervals characterized by the prevalence of circularly polarized fast magnetosonic/whistler waves.…”
Section: Velocity Driftmentioning
confidence: 99%
“…The SOP is inversely correlated with k B , 0 ( ) q . This indicates that the orthogonal components have a higher coherence at small propagation angles, and thus the quasi-parallel-propagating fluctuations are more wave-like (He et al 2022;Zhu et al 2023). At small propagation angles, the SOP is slightly greater at τ < 100 s than at τ > 100 s. The ellipticity distribution is isotropic at a constant period.…”
Section: Turbulent Energy Anisotropy Of Inertial-range Turbulencementioning
confidence: 95%